New insights into physics of explosive water boiling derived from molecular dynamics simulations. (June 2021) - Ilic, Milica; Stevanovic, Vladimir D.; Milivojevic, Sanja; Petrovic, Milan M.
Highlights: Explosive boiling of thin water film on hot cooper substrate is investigated. Investigations are based on results of Molecular Dynamics simulations. Quantitative analysis of involved explosive boiling mechanisms is done. The results show that explosive boiling comprises several phases. Abstract: In this paper the dynamics of explosive boiling of a 72 Å thick water film on the hot copper substrate with the plain surface is analysed. The analyses are based on the results of molecular dynamics (MD) simulations of the transient in which the thermostat temperature within the solid substrate is increased from 298 to 800K. The obtained results show that explosive boiling comprises several phases. The first phase involves rapid thermoacoustic pressure build-up in the near wall region due to intensive water heating and its volumetric expansion. The generated compression wave propagates through the liquid film reaching the peak value higher than critical water pressure. Due to reflection at the free film surface the original compression wave turns into an expansion wave. This event leads to a rapid pressure decrease and occurrence of tension stress. The second phase starts when the pressure enters the negative domain. This phase is accompanied with nucleation of vapour embryos and their subsequent growth in the superheated water layer in the near wall region. As the intensity of vapour phase generation is moderate, the liquid film in this phase is still exposed to tension. The stress recovery starts in the third phase when the water temperature in the near wall layer attains the spinodal value. This leads to a massive vaporization, nanobubble coalescence and thermal explosion, which causes spallation of the liquid film and lift-off of the liquid slug. The last phase is characterized by suppression of heat transfer by the expanding vapour layer. As a consequence, after reaching the maximum, the pressure decreases. This paper gives quantitative description and detailed insight into the mechanisms associated with each of the aforementioned phases.